The effects of Clostridium butyricum on Ira rabbit growth performance, cecal microbiota and plasma metabolome - Ye, Xiao Xing; Li, Ke Yao; Li, Ya Fei; Lu, Jia Ning; Guo, Ping Ting; Liu, Hao Yu; Zhou, Li Wen; Xue, Shuai Shuai; Huang, Cai Yun; Fang, Shao Ming; Gan, Qian Fu (Frontiers in Microbiology, 2022)
Clostridium butyricum (C. butyricum) can provide many benefits for animals’ growth performance and gut health. In this study, we investigated the effects of C. butyricum on the growth performance, cecal microbiota, and plasma metabolome in Ira rabbits. A total of 216 Ira rabbits at 32 days of age were randomly assigned to four treatments supplemented with basal diets containing 0 (CG), 200 (LC), 400 (MC), and 600 mg/kg (HC) C. butyricum for 35 days, respectively. In comparison with the CG group, C. butyricum supplementation significantly improved the average daily gain (ADG) and feed conversion rate (FCR) at 53 and 67 days of age (P < 0.05) and digestibilities of crude protein (CP) and crude fiber (CF) at 67 days of age (P < 0.05). The cellulase activity in the HC group was higher respectively by 50.14 and 90.13% at 53 and 67 days of age, than those in the CG groups (P < 0.05). Moreover, at 67 days of age, the diet supplemented with C. butyricum significantly increased the relative abundance of Verrucomicrobia at the phylum level (P < 0.05). Meanwhile, the concentrations of different metabolites, such as amino acids and purine, were significantly altered by C. butyricum (P < 0.05). In addition, 10 different genera were highly correlated with 52 different metabolites at 53-day-old and 6 different genera were highly correlated with 18 different metabolites at 67-day-old Ira rabbits. These findings indicated that the C. butyricum supplementation could significantly improve the growth performance by modifying the cecal microbiota structure and plasma metabolome of weaned Ira rabbits.